Unfavorable conditions for adolescent’s vocational choice in Peru - Osores Queirolo, Silvia Hilda (2021)
This essay aims to analyze the main educational causes that prevent adolescents from making a vocational choice that allows them to live this process satisfactorily, as part of their personal development. Publications from 2017 and 2020 were analyzed, they came from the Ministry of Education (MINEDU), National Institute of Statistics and Informatics (INEI), Institute of Peruvian Studies (IEP), Organization for Economic Co-operation and Development (OECD), National Superintendence of University Higher Education (SUNEDU) and World Bank, in addition to other publications of vital interest related to adolescence and vocation. Therefore, the following research questions arise: Why do youths interrupt their personal education? Is it enough for youths to be sure about their vocation? What role does the school play in this process? Based on the results, it was concluded that there are deficient structural factors, from basic education to higher education, which prevent a suitable preparation in both academic and personal. In addition, improvements in the supervision of national curriculum implementation, among others, are recommended